2020
DOI: 10.1111/os.12668
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Study on the Stress Distribution of the Knee Joint After Tibial Fracture Malunion with Residual Varus–Valgus Deformity

Abstract: ObjectiveTo investigate the effect of residual varus and valgus deformity on the stress distribution of the knee joint after tibial fracture malunion.MethodsFourteen adult cadaver specimens were selected to establish the models of tibial fractures, which were fixed subsequently at neutral position (anatomical reduction) and malunion positions (at 5°, 10°, and 15° valgus positions, and 5°, 10°, and 15° varus positions). The stress distribution on the medial and lateral plateau of the tibia was quantitatively me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…14 There is evidence to support contributions from the mechanical hypothesis from biomechanical, animal, and human studies. Biomechanical investigations have demonstrated varus/valgus deformity asymmetrically increases monolateral compartment joint pressure by 50%, 17 and rabbit studies have confirmed overloading and cartilage damage in the theoretically overloaded compartments. 18 Clinical studies of malunion have been less consistent, perhaps related to study design and flaws in the analysis of the associated deformities.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is evidence to support contributions from the mechanical hypothesis from biomechanical, animal, and human studies. Biomechanical investigations have demonstrated varus/valgus deformity asymmetrically increases monolateral compartment joint pressure by 50%, 17 and rabbit studies have confirmed overloading and cartilage damage in the theoretically overloaded compartments. 18 Clinical studies of malunion have been less consistent, perhaps related to study design and flaws in the analysis of the associated deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that an individual with tibial fractures that heal with residual deformity may have increased risk of pain and stiffness in knee and ankle joints. Residual varus and valgus deformity after tibial fracture malunion can lead to obvious changes of the stress distribution of the knee joint 8,9 . Therefore, tibial fractures should be reduced anatomically and fixed rigidly to avoid residual varus-valgus deformity and malalignment of lower limbs 10 .…”
Section: Discussion:-mentioning
confidence: 99%
“…As the pressure-sensitive lm material change with the humidity and temperature, the color development is also different. Therefore, humidi ers and air conditioners are used in this experiment to keep the indoor temperature at 25 ~ 30℃ and the relative humidity at 35% RH ~ 80% RH [22]. FPD-305E densitometer and FPD-306E pressure transducer (Fuji Company, Japan) were used to read the stress values of the ultra-low pressure sensitive lms.…”
Section: Methodsmentioning
confidence: 99%